Relationship between cognitive avoidant coping and changes in overgeneral autobiographical memory retrieval following an acute stressor - Debeer, E; Raes, F; Claes, S; Vrieze, E; Williams, J; Hermans, D (2012)
According to the functional avoidance hypothesis, overgeneral autobiographical memory, the tendency to retrieve personal memories in a less specific format, might serve an affect-regulating function. Reducing the specificity of memories of negative events may prevent individuals from re-experiencing the associated painful emotions. This cognitive avoidance strategy might not only be employed by depressed and traumatized patients, but also by healthy individuals. In the present study we tested the hypothesis that the increase in memory overgenerality induced by an acute stressor is positively correlated with habitual (cognitive) avoidant coping. Participants (N = 32) were exposed to a Trier Social Stress Test. Cognitive avoidant coping was measured at the start of the experiment by means of the Mainz Coping Inventory. Before, immediately after, and 40 min after the Trier Social Stress Test, autobiographical memory specificity was assessed by means of the Autobiographical Memory Test. Cognitive avoidant coping was significantly correlated with an increase in categoric memories from pre to immediately post stressor, but not with change in overgeneral memories from pre to 40 min post stressor. The results of the present experiment provide further support for functional avoidance as one of the mechanisms underlying overgeneral memory. © 2010 Elsevier Ltd. All rights reserved.